2020
DOI: 10.3390/cells9010154
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A/EMMPRIN Axis Is Involved in Pro-Fibrotic Processes Associated with Thoracic Aortic Aneurysm of Marfan Syndrome Patients

Abstract: Background: Marfan syndrome (MFS) is a genetic disease, characterized by thoracic aortic aneurysm (TAA), which treatment is to date purely surgical. Understanding of novel molecular targets is mandatory to unveil effective pharmacological approaches. Cyclophilin A (CyPA) and its receptor EMMPRIN are associated with several cardiovascular diseases, including abdominal aortic aneurysm. Here, we envisioned the contribution of CyPA/EMMPRIN axis in MFS-related TAA. Methods: We obtained thoracic aortic samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It is well documented that CypA positively participates in cancer metastasis via type III EMT in colorectal cancer (Yamamoto et al, 2020) and lung cancer (Guo et al, 2018). In addition, CypA plays roles in tissue fibrosis, such as myocardial fibrosis (Seizer et al, 2012), thoracic aortic aneurysm fibrosis (Perrucci et al, 2020), and oral submucous fibrosis (Yuan et al, 2016). However, it is not clear whether CypA has an influence on type II EMT.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that CypA positively participates in cancer metastasis via type III EMT in colorectal cancer (Yamamoto et al, 2020) and lung cancer (Guo et al, 2018). In addition, CypA plays roles in tissue fibrosis, such as myocardial fibrosis (Seizer et al, 2012), thoracic aortic aneurysm fibrosis (Perrucci et al, 2020), and oral submucous fibrosis (Yuan et al, 2016). However, it is not clear whether CypA has an influence on type II EMT.…”
Section: Discussionmentioning
confidence: 99%
“…EMMPRIN is abundantly expressed in the cells and pathological tissues associated with TAAs [ 7 ]. Our study found that EMMPRIN levels were elevated in MFS TAA tissue, suggesting that, in MFS, the secretion of EMMPRIN is blocked, causing higher EMMPRIN abundance in the cells and tissue.…”
Section: Discussionmentioning
confidence: 99%
“…EMMPRIN is released into circulation through the secretion of extracellular vesicles and this process has been demonstrated to be dependent upon hydrolysis by the Membrane Type-1 MMP (MT1-MMP), also known as MMP-14 [ 3 , 4 ]. Both MT1-MMP and EMMPRIN are elevated in TAA tissue [ 5 , 6 , 7 ]. In other diseases, EMMPRIN abundance is often increased in both the pathological tissue and circulation [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other compounds provided, in the last years, promising results both in vivo and in vitro within MFS-TAA context [ 56 , 57 ]. Among worth of mention compounds, there are androgen inhibitors [ 58 ], folic acid [ 59 ], inhibitors of soluble guanylate cyclase [ 60 ], NAD [ 61 ], and apocynin [ 62 ], all displaying interesting in vivo outcomes by reducing TAA progression.…”
Section: Background On Thoracic Aortic Aneurysmmentioning
confidence: 99%